Present status of quail farming in Africa: A review - John Cassius Moreki; Shame Bhawa; Leungo P. Kamwanga; Lindile Chiwaya; Bolokang Kgosidintsi; Mogi Moreki; Ndaleh Nghonjuyi; Akinyele Adesehinwa (Poultry Science Journal)
Although quail farming is still in its infancy in Africa, it is commonly practiced in Asia, with China producing about 38% of global production. About 10% of the world’s egg production comes from quail, while their meat represents about 0.2% of the global poultry meat production. This review presents the status of quail farming in Africa and highlights the sub-sector’s challenges and opportunities. Quail farming is one of the least exploited poultry sub-sectors on the African continent; hence, there is limited production and consumption data. The consumption of quail meat and eggs is still low in Africa, but these have the potential to flourish as people become more aware of their nutritional and health benefits. As an evolving industry with great potential, quail farming faces many challenges, including a lack of access to markets, lack of access to credit, inadequate extension support, unavailability of specific quail feeds, and poor housing. Many opportunities exist in feed manufacturing, expanding existing hatcheries and establishing new ones, establishing breeding and rearing facilities, and further processing of quail meat and eggs. Some potential identified challenges include intensifying farmer education, forming cooperative societies to improve market access, developing support programs to encourage farmers to venture into quail farming, and investing in affordable and durable housing to mitigate theft, predation and escaping. We conclude that African governments should consider encouraging quail farming, as it has the potential to play an important role in income generation, job creation and food and nutrition security.